Combination Adjuvants Enhance Recombinant H5 Hemagglutinin Vaccine Protection Against High-Dose Viral Challenge in Chickens - Yanjuan He; Jiaxin Wang; Lanyan Chi; Yajing Dong; Huixin Chen; Xiaocui Meng; Ming Liao; Yongwen Luo; Huiying Fan (Vaccines)
Background: Recombinant avian influenza subunit vaccines often require adjuvants to enhance immune responses. This study aims to evaluate the immune-enhancing potential of seven combination adjuvants in specific pathogen-free (SPF) chickens. Methods: SPF chickens were vaccinated with combinations of ISA78VG and adjuvants, including Quil-A, CpG, and monophosphoryl lipid A (MPLA). Their immune responses were assessed using a vaccination and viral challenge protection model. Results: The combinations of ISA78VG with Quil-A, CpG&MPLA or CpG&Quil-A significantly enhanced antibody responses and provided cross-protection against the H5N8-20135 strain. The ISA78VG&MPLA and ISA78VG&CpG&MPLA combinations induced the stronger IFN-γ production, with CpG further amplifying the immune response. The ISA78VG&Quil-A formulation, in particular, stimulated rapid antibody responses, achieving a 100% seroconversion by day 14 and high titers of hemagglutination inhibition (HI) antibodies against both the recombinant HA antigen and the H5N6-20053 virus. Conclusions: The ISA78VG&Quil-A combination is an ideal adjuvant for enhancing the immunogenicity of avian influenza rHA subunit vaccines, offering a promising strategy for H5 subtype vaccine development.